Implementation of Disaster Risk Reduction Education in SD Muhammadiyah Condongcatur 2 - Nugraheni, Yumidiana Tya; Firmansyah, Agus (Proceeding International Conference on Religion, Science and Education, 2025)
This research is an effort to reduce disaster risk in educational institutions, especially Muhammadiyah Condongcatur 2 Elementary School. This study is a qualitative study with a case study type. Data acquisition was carried out through observation, documentation, and interviews. The data analysis consists of data condensation, data display, and conclusions. This study aims to: first, determine the implementation of PRB in SD Muhammadiyah Condongcatur 2. Second, determine the obstacles to PRB in SD Muhammadiyah Condongcatur 2. The results of the study are: The implementation of PRB in SD Muhammadiyah Condongcatur 2 is carried out in stages. The components of PRB that have been implemented include aspects of preparation and training and education for educators and staff. The two stages have produced several analyses, including disaster history, multi-sector disaster threat analysis, vulnerability analysis, capacity analysis, and standard procedures for flood disasters. The obstacles to implementing the three stages of PRB have not been optimally understood, and additional training is needed to strengthen them.